REVOLUTIONIZING ANIMATION: IS ARTIFICIAL INTELLIGENCE (AI) CAPABLE OF EQUALIZING THE ANIMATION INDUSTRY QUALITY? - Selvan.N, Tamil; Subramaniam, Valarmathi (International Journal of Research -GRANTHAALAYAH, 2024)
The paper explores the transformative impact of artificial intelligence (AI) on the animation industry, examining whether AI can truly equalize the quality of animation across various studios and creators. While AI technologies have advanced significantly, enabling faster production processes and enhancing creative possibilities, this study argues that AI cannot fully replicate the refined artistry and emotional depth inherent in traditional animation. By analyzing case studies of AI-generated animations alongside works from established animators, the research highlights the limitations of AI in capturing the subtleties of human expression and storytelling. Ultimately, AI can serve as a powerful tool to increase animation production; it cannot replace the unique creative vision and craftsmanship that define high-quality animation, suggesting a future where AI and human artists collaborate rather than compete.